PERAN TERPAAN MEDIA SOSIAL DALAM PERUBAHAN PERSEPSI KHALAYAK TERHADAP KAUM HOMOSEKSUAL - Glorya Agustiningsih (Jurnal Komunikasi dan Bisnis, 2018)
Todayâ€™s modern society is facing rapid changes of communication technology impacts in all aspects, not only on the individual basis but also in the larger aspects, such as social life, cultural, political, business, education, and many more. One great example of communication technology products which has a significant impact on the society is social media. Indonesia itself could be stated as a country with social media users are pretty high which caused by the digital trend and high mobile penetration. Because of the magnitude effects of social media changes many aspects in society that it could bring out either negative or positive effects at the same time. Hence, this paper examines concepts of how social media gives a contribution on transformation of perception in society towards homosexuals for as we know the existence of homosexuals is still being debated in Indonesia for some reasons. The method used in this study are qualitative approach which uses interview data, literature and documentation studies to provide valuable concepts about role of social media. Â Keywords: social media, homosexuals, perception, communication technology